Transforming Caribbean agriculture. - SEGAL, Aaron (1996)
Analyses the persistent problem of export and domestic stagnation in Caribbean agriculture. Examines the potential offered by biotechnology and other innovative technologies to raise yields and generate exports. Concludes that certain of these technologies have the capability of ending the long-term stagnation of Caribbean agriculture.